Análisis Financiero en la Empresa Comercial “Genesis Celular” de la Ciudad De Loja, Periodos 2019 – 2020 - Malla Malla, Josselyn Tatiana (2022)
The curricular integration work entitled FINANCIAL ANALYSIS IN THE COMMERCIAL COMPANY "GENESIS CELULAR" OF THE CITY OF LOJA, PERIOD 2019 - 2020, allows to comply with the proposed objectives and that refers to performing a vertical and horizontal analysis and application of financial indicators, to obtain a diagnosis on the actual state of the company, to know the economic and financial position. The methodology applied for its execution consisted of gathering safe and reliable information from the owner, complying with the objectives set, the vertical and horizontal analysis of the Balance Sheet and the Income Statement for the periods 2019 - 2020 was performed, to establish the degree of participation of each account and determine the variations of assets, liabilities, equity, income, costs, and expenses with their respective graphical representation and interpretation. Subsequently, the financial indicators of liquidity, activity, indebtedness, and profitability were applied, which show the company's performance, strengths, and weaknesses, detecting the areas that need more attention with their respective interpretations and graphs, necessary to evaluate the financial, economic, and operational performance of the company. Also, through the Dupont System, the return on assets and equity was applied to show the results concerning the generation of profits; however, this performance is not considered satisfactory since the company has the possibility of increasing its profit by using its resources adequately and that the rotation of assets improved but did not allow generating greater benefits for the company due to the increase in sales costs caused by the COVID-19 pandemic; The value added (EVA) after covering its costs can be considered satisfactory, which is why it is deduced that the company can generate added value, which favors the company's profitability. Finally, the Financial Analysis Report was presented, communicating the results obtained to the company's owner, making known the comments, conclusions, and, recommendations for making correct and timely decisions to improve the company's financial management. The work concludes that the company since its inception has not made the application of financial indicators, so it did not allow to know its financial situation during these periods studied, so possible alterations that affect the development and growth of the company can be avoided, which merits recommending to the manager - owner the application of indicators that 5allow measuring liquidity, activity, indebtedness and profitability, so that corrective measures can be taken, necessary and in time, to avoid any alteration that may occur in the company.